2020
DOI: 10.17515/resm2019.168ea1204
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different cases of soft story formation for mid-rise RC buildings

Abstract: Soft story irregularity is one of the main reasons of the building damage during past earthquakes and has been mentioned in almost all reconnaissance reports. Soft story due to increased story height is a recognized subject but soft story may also arise due to abrupt changes in amount of infill walls between stories, which are usually not considered as a part of load bearing system. This study investigates soft story behavior due to increased story height, lack of load bearing infill walls at ground story and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…In this case, the soft story mechanism is formed and the ground floors in particular experience the collapse mechanism. This situation has been observed frequently in buildings where there are large commercial enterprises on the ground floors and there are residential sections on the upper floors [52][53][54][55]. In Adıyaman, it is observed that considerable structural damage occurred,…”
Section: Soft/weak Storymentioning
confidence: 96%
“…In this case, the soft story mechanism is formed and the ground floors in particular experience the collapse mechanism. This situation has been observed frequently in buildings where there are large commercial enterprises on the ground floors and there are residential sections on the upper floors [52][53][54][55]. In Adıyaman, it is observed that considerable structural damage occurred,…”
Section: Soft/weak Storymentioning
confidence: 96%